Prevalence of Rheumatoid Arthritis and DMARDs Usage in Indian Population: A Cross-Sectional Study - Goud, Dr. Thirumaleswara (Asian Journal of Pharmaceutics (AJP), 2021)
Background: Rheumatoid arthritis (RA) is an autoimmune disorder characterized by symmetric and erosive synovitis with extra-articular involvement in some cases. RA prevalence in India is 0.75%. The study is to estimate the prevalence of RA in the South Indian population and to determine the demographic characteristics such as gender, age, geographical locality, and usage of antirheumatic drugs. Methodology: This prospective cross-sectional study was conducted in 600 patients of both male and female at advance rheumatology center. The patients were selected based on inclusion and exclusion criteria. Patients who are suspected and diagnosed newly with RA, patients who are already with RA attending the rheumatoid center and are on therapy, and patients age equal to and above 16 years either gender are included in the study. Patients with other arthritic and immunologic problems such as osteoarthritis, psoriatic arthritis, systemic lupus erythematosus, spondylosis, and osteoporosis were excluded from the study and patient’s age below 16 years are excluded from the study. Results: Among 600 patients presented to advance rheumatology center, 174 patients are identified with classical symptoms of RA, in those female and male patients are 132 and 42, respectively. The mean age of total patients is 45.51 ± 12.09. The estimated prevalence was found to be 0.29 or 29% (95% confidence interval is 0.25–0.33). Disease-modifying antirheumatic drugs (36.9%) are mostly prescribed. Conclusion: This study witnessed a rise in the prevalence of RA in South Indian population which gives alarming signals to the health authority and policymakers to increase the awareness on RA in India.